Keabsahan Pembuatan Akta Pemberian Hak Tanggungan Atas Sertipikat Hak Guna Bangunan Pada Rumah Susun yang Telah Dilakukan Perjanjian Pengikatan Jual Beli - Nahdlotul Fadilah (Fakultas Hukum Universitas Airlangga, 2021)
Developer as seller and/or marketing agency often promising everything to buyers related to the flats settlement process, can be regulated in Sale and Purchase Engagement Agreement (hereinafter referred as “PPJB”) accordance with Article 43 of Law Number 20 of 2011 concerning Flats (hereinafter referred as “Flat Law”) and Regulation of Minister of Public Works and Public Housing Number 11/PRT/M/2019 concerning the Preliminary House Sale and Purchase Agreement System (hereinafter referred as “Ministerial Regulation of PUPR No. 11/PRT/M/2019”). The purpose of this research is to analyse the basis of validity of the Akta Pemberian Hak Tanggungan (Security Title Provision Deed, hereinafter referred as “APHT”) on the Building Rights Certificate of the Flats (hereinafter referred as “HGB”) after the PPJB has been implemented, and to analyse legal protection for buyers when the certificate of HGB is guaranteed after PPJB is carried out. The research has been determined that PPJB has classified as a conditional engagement because it has regulated the points of the agreement and has a legal consequences. The seller/developer who will enact the object of PPJB as a guarantee, basis of validity an APHT at certificate of HGB’s Flats after regulated a PPJB have to qualify Article 11 of UUHT and pay attention to the provisions of Article 10 paragraph (3) alphabet d of Ministerial Regulation of PUPR No. 11/PRT/M/2019. Legal protection for buyers is a preventive legal protection and repressive legal protection.Keywords: Validity an APHT; Certificate of HGB’s Flat; PPJB; Legal Protection for Buyers.Developer sebagai penjual dan/atau agen pemasaran sering kali menjanjikan segala sesuatu kepada pembeli terkait proses penyelesaian rumah susun, dituangkan dalam perjanjian pengikatan jual beli (PPJB) sesuai Pasal 43 Undang-Undang Nomor 20 Tahun 2011 tentang Rumah Susun (UU Rumah Susun) dan Peraturan Menteri Pekerjaan Umum dan Perumahan Rakyat Nomor 11/PRT/M/2019 tentang Sistem Perjanjian Pendahuluan Jual Beli Rumah (Permen PUPR No. 11/PRT/M/2019). Penelitian ini bertujuan untuk menganalisis dasar keabsahan akta pemberian hak tanggungan (APHT) atas sertipikat hak guna bangunan (HGB) pada rumah susun yang telah dilakukan PPJB dan menganalisis bentuk perlindungan hukum bagi pembeli apabila sertipikat HGB pada rumah susun dijaminkan setelah dilakukan PPJB. Dalam penelitian ini ditemukan bahwa PPJB digolongkan sebagai perjanjian bersyarat karena sudah menyentuh pokok-pokok perjanjian dan telah menimbulkan akibat hukum. Penjual/developer yang akan menjadikan objek PPJB sebagai jaminan, dasar keabsahan pembuatan APHT atas sertipikat HGB pada rumah susun yang telah dilakukan PPJB harus memenuhi ketentuan Pasal 11 UUHT dan memperhatikan ketentuan Pasal 10 ayat (3) huruf d Permen PUPR No. 11/PRT/M/2019. Bentuk perlindungan hukum bagi pembeli satuan rumah susun dapat berupa perlindungan hukum preventif dan perlindungan hukum represif.Kata Kunci: Keabsahan APHT; Sertipikat HGB Pada Rumah Susun; PPJB; Perlindungan Hukum Pembeli.